Heavy Metal Levels of Lead and Cadmium in Baronang Fish from South Sulawesi, Indonesia - Ikhtiar, Muhammad; Mahmud, Nur Ulmy; Yusuf, Rezky Aulia; Amir, Haeril (Gaceta Médica de Caracas, 2022)
Objective: The purpose of this study was to determine the content of the heavy metals in the Baronang fish at Kayu Bangkoa pier and the Kera-Kera Pier in the Makassar city, South Sulawesi, Indonesia in 2020. Methods: This was an observational descriptive approach research. The accidental sampling technique was used at two locations, Kayu Bangkoa pier, and Kera-Kera pier. Baronang fish samples were taken using fishing rods or nets and each bait was examined and analyzed in the laboratory.